1)x^2+9x+8 (x+1)(x+8) (x+8)
==
3x^2+8x+5 3(x+1)(x+1 2/3) 3x+5
x^2+9x+8=0 3x^2+8x+5=0
D= 8^2-4*3*5=64-60=4
x1+x2=-9| -8(+)-))2
x1,2=
|-8;-1 6
x1x2=8 | x1=-1 ; x2=-1 2/3
2)
a)x(x+3)-4(x-5)=7(x+4)-8
x^2+3x-4x+20=7x+28-8
x^2-8x=0
x(x-8)=0
x=0 или х-8=0
х=8
б)2x^4-9x+4=0
D=(-9)^2-4*2*4=81-32=49
9(+(-))7
x1,2=
4
x1=4; x2=0.5
получим 2 уравнения:
1) 4tgx + 3tgx = sin2x
2) 4tgx - 3tgx = sin2x
1) 7tgx = 2sinxcosx
7sinx/cosx = 2sinxcosx
7 = 2cos^2x
cos^2x = 3,5
cosx = +- 1,87
нет решений
2)
tgx = 2sinxcosx
sinx/cosx = 2sinxcosx
1 = 2cos^2x
cos^2x = 0,5
cosx = +-1/(2)^0,5
x = П/4 + Пk/2